The Complete Mitochondrial Genome and Expression Profile of Mitochondrial Protein-Coding Genes in the Bisexual and Parthenogenetic Haemaphysalis longicornis - Wang, Tianhong; Zhang, Shiqi; Pei, Tingwei; Yu, Zhijun; Liu, Jingze (Frontiers in Physiology, 2019)
The tick Haemaphysalis longicornis is widely distributed in eastern Asia, New Zealand and Australia, and is well-known as a vector of multiple zoonotic pathogens. This species exhibits two reproductive strategies, bisexual and obligate parthenogenetic reproduction. Hence, in the current study, the complete mitochondrial genomes of the bisexual and parthenogenetic populations were assembled and analyzed, and the expression of the mitochondrial protein-coding genes was evaluated and compared between the two reproductive populations. The results indicated that the length of the mitochondrial genomes of the two reproductive populations is 14,694 and 14,693 bp in the bisexual and parthenogenetic populations, respectively. The AT content in the mitochondrial genome of the bisexual and obligate parthenogenetic population reached 77.22 and 77.34%, respectively. The phylogenetic tree was constructed combining 13 protein-coding genes, which showed that the genetic distance between the bisexual and parthenogenetic populations was less than that between the subspecies. The expression of the mitochondrial protein-coding genes was quantitatively analyzed at different feeding status for the bisexual and parthenogenetic populations, and the results showed significant differences in the expression patterns of these genes, suggesting that they might trigger specific energy utilization mechanisms due to their different reproductive strategies and environmental pressures.